Africa Stock Markets Cross-Market Linkages: A Time-Varying Dynamic Conditional Correlations (DCC-GARCH) Approach - Marozva, Godfrey (Journal of Applied Business Research, 2017)
This article investigates stock return volatility and contagion among the five African countries (Zimbabwe, South Africa, Egypt, Kenya, and Nigeria) and the United States of America for the period between 1998 and 2015. Engle (2002)’s Dynamic Conditional Correlation multivariate generalized autoregressive conditional heteroscedasticity model was adapted to explore the time-varying conditional correlations to capture the contagion behavior of these financial markets over time. In this article the researchers observes that South African Stock returns are highly correlated to NYSE stock returns and the coefficients are significant for all periods under consideration. Additionally, the South African stock returns are significantly negatively related to Zimbabwean stock returns. An analysis of correlation confirms what most scholars found, that the correlations amongst markets tend to increase during the time of crises and weaken during periods of stability with an exception of Egypt whose results indicate an insignificant negative correlation during the 2007/9 crisis. It is recommended that future research in this area should focus on the potential contagion mechanisms between African countries and European countries especially looking at what transpired during and after the sovereign debt crisis.
Keywords: Stock Market Returns; Volatility; Contagion; Inter Linkages; Global Crisis; Portfolio Diversification; GARCH; Dynamic Conditional Correlations